Influence of surgical manipulation and surgical modality on the molecular detection of circulating tumor cells from colorectal cancer - Park, Soo Yeun (The Korean Surgical Society, 2012)
PURPOSE: The aim of this study was to evaluate the relationship between the detection of circulating tumor cell molecular markers from localized colorectal cancer and the time-course of a surgical manipulation or surgical modality. METHODS: From January 2010 to June 2010, samples from the peripheral blood and the inferior mesenteric vein were collected from 42 patients with cancer of the sigmoid colon or rectum. Pre-operative, intra-operative (both pre-mobilization and post-mobilization), and post-operative samples were collected. We examined carcinoembryonic antigen (CEA) mRNA and cytokeratin-20 (CK20) mRNA by real-time reverse-transcriptase polymerase chain reaction. Changes in mRNA detection rates were analyzed according to the time of blood sample collection, the surgical modality, and patient clinicopathological features. RESULTS: mRNA expression rates before surgical resection did not differ between blood samples from the peripheral and inferior mesenteric veins. The detection rate for CEA and CK20 mRNA showed a tendency to increase after operative mobilization of the cancer-bearing bowel segment. Furthermore, the cumulative detection rates for CEA and CK20 mRNA increased significantly over the course of surgery (pre-mobilization vs. post-mobilization). The cumulative detection rate decreased significantly after surgical resection compared with the pre-operative rates. However, no significant difference was observed in the detection rates between different surgical modalities (laparoscopy vs. open surgery). CONCLUSION: The results of this study suggest that surgical manipulation has a negative influence on the dissemination of circulating tumor cells during operations on localized colorectal cancer. However, the type of surgical technique did not affect circulating tumor cells.